Palm trees and fruits residues : recent advances for integrated and sustainable management (Academic Press, 2022)
Palm Trees and Fruits Residues: Recent Advances for Integrated and Sustainable Management places the wastes of palm trees and fruit residues in the international context of sustainable development, providing sustainable applications that are detailed based on sector to help readers from specific fields identify applications. Furthermore, successful processing case studies using valorization are presented. As the expansion of palm tree fruit crops processing industries (manufacture of syrup, honey, non-alcoholic beverages, flours, confectionery products, fruit paste, etc.) is generating growing quantities of wastes in different forms, this book covers sustainable aspects. Written by an international team of contributors, this title is aimed at professionals and enterprises who aspire to develop real, high-scale industrial applications for palm tree and fruit residue valorization.